Pemberdayaan Masyarakat Desa Melalui Wirausaha Untuk Usia Produktif - Ardianingsih, Arum; Sulistiyaningsih , Riski (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
The village community empowerment is an effort to develop self-sufficiency and prosperity by increasing knowledge, attitudes, skills, behaviour, abilities, awareness, and utilizing resources through the establishment of policies, programs, activities and assistance according to the conditions of the local community. The community empowerment can be done by introducing about starting to open a business (entrepreneurship). Kutosari village, Doro sub-district, Pekalongan regency has considerable potential in agriculture and animal husbandry. The villagers generally become laborers and migrate to work. Potential in the form of optimally processed agricultural and livestock products will provide economic value. The purpose of implementing community service activities is to provide additional knowledge and skills to start and manage a business. The method of implementing community service is training with games and practice of preparing business plans. The activity participants are productive age people in Kutosari village. The result of the activity is that the community is able to explore business ideas and prepare a business plan to be carried out. The community is becoming more concerned that the village potential they have can provide economic value. The community are becoming more aware that the entrepreneurship will improve their welfare.